Pelatihan Content Creator Dengan Tema Prospek Bisnis Yang Menjanjikan Pada Masyarakat Desa Panjunan, Kecamatan Sukodono, Kabupaten Sidoarjo, Sebagai Bentuk Meningkatkan Kompetensi Mahasiswa Oleh Mahasiswa Universitas Sunan Giri Surabaya - Mahfud Ilham; Mahbubah Lihani; Muchammad Catur Rizky; Wulandari Wulandari; Misbachul Munir; Eli Retnowati; Didit Darmawan; Cilda Thesisa Ilmawan Dzinnur (Asosiasi Riset Pendidikan Agama dan Filsafat Indonesia, 2023)
This research is a remarkable initiative that aims to empower villagers, especially kartars and local communities, to understand and harness the power of digital content for education, promotion, and social empowerment. The training consists of various factors in the world of digital content, including photography, writing, online marketing, and social media management. The method of implementing community service program activities begins with an approach to students of Sunan Giri University Surabaya, using methods known as Participatory Action Research (PAR), Asset-Based Community Development (ABCD), and a mixed approach. Activities were carried out in the Hall of Panjunan Village Hall, Sukodono District. The methods applied involved implementation methods in community service programs as well as training and counseling methods. The active involvement of the participants, creating strong cooperation between students and the community, thus creating a sustainable positive impact in the utilization of digital content to improve the quality of life and community empowerment.